2023
DOI: 10.3389/fpsyg.2023.1089566
|View full text |Cite
|
Sign up to set email alerts
|

How do goats “read” 2D-images of familiar and unfamiliar conspecifics?

Abstract: To study individual recognition in animals, discrimination tasks are often conducted by presenting 2D images of real conspecifics. However, animals may discriminate the images merely as visual stimulus combinations without establishing referential relationships to the individuals depicted. In the current study, we investigated whether goats are able to discriminate photos of familiar and unfamiliar conspecifics, whether they not only process the photos as visual stimuli, but also understand them as virtual cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
0
3
1
Order By: Relevance
“…However, their response did not differ between familiar and unfamiliar individuals (irrespective of species), suggesting that goats either cannot spontaneously assign social recognition categories to 2D images or were equally motivated to pay close attention to both categories (but for different reasons). These findings are partly in contrast to related research on goats and other domestic ungulate species (Coulon et al, 2011;Langbein et al, 2023) and thus raise questions about the comparability of test designs.…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…However, their response did not differ between familiar and unfamiliar individuals (irrespective of species), suggesting that goats either cannot spontaneously assign social recognition categories to 2D images or were equally motivated to pay close attention to both categories (but for different reasons). These findings are partly in contrast to related research on goats and other domestic ungulate species (Coulon et al, 2011;Langbein et al, 2023) and thus raise questions about the comparability of test designs.…”
Section: Discussioncontrasting
confidence: 98%
“…In contrast to this, results from other ruminants, such as cattle (Coulon et al, 2011) and sheep (Peirce et al, 2000(Peirce et al, , 2001, have shown that a set of ruminant species have the capability to form this concept using two-dimensional head cues in a visual discrimination task. Langbein et al (2023) also found some evidence that goats are able to associate two-dimensional representations of conspecifics with real animals in a visual discrimination task. It is therefore surprising to see that the subjects in our study did not show differential looking behaviour with respect to the familiarity of the individuals presented.…”
mentioning
confidence: 87%
See 2 more Smart Citations